2022
DOI: 10.3390/jpm12020269
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a), Immune Cells and Cardiovascular Outcomes in Patients with Premature Coronary Heart Disease

Abstract: The detection of lipoprotein(a) [Lp(a)] in the artery wall at the stage of lipid-bands formation may indicate that it participates in the atherosclerosis local nonspecific inflammatory process. Innate immune cells are involved in atherogenesis, with monocytes playing a major role in the initiation of atherosclerosis, while neutrophils can contribute to plaque destabilization. This work studies the relationship between Lp(a), immune blood cells and major adverse cardiovascular events (MACE) in patients with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
13
1
1
Order By: Relevance
“…Whilst absolute cutoffs may be beneficial for decision making within the clinic, a linear increase in atherosclerotic CVD risk has been observed with Lp(a) concentration, suggesting that even a modest increase in Lp(a) may be determinantal ( 23 ). Notably, within this study, the observation that no difference was found between low (<30 mg/dl) and elevated (30–50 mg/dl) Lp(a) in ACS risk differs from recent findings, where Lp(a) levels over 30 mg/dl contributed to an increased risk of coronary heart disease ( 44 ) and a linear relationship with both fatal and nonfatal cardiovascular risk ( 45 , 46 ). This may, in part, be due to the disparity in race between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Whilst absolute cutoffs may be beneficial for decision making within the clinic, a linear increase in atherosclerotic CVD risk has been observed with Lp(a) concentration, suggesting that even a modest increase in Lp(a) may be determinantal ( 23 ). Notably, within this study, the observation that no difference was found between low (<30 mg/dl) and elevated (30–50 mg/dl) Lp(a) in ACS risk differs from recent findings, where Lp(a) levels over 30 mg/dl contributed to an increased risk of coronary heart disease ( 44 ) and a linear relationship with both fatal and nonfatal cardiovascular risk ( 45 , 46 ). This may, in part, be due to the disparity in race between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Cai et al found that a lower LMR at admission was independently associated with long-term all-cause mortality and major adverse cardiac events after discharge in patients with ST-elevation myocardial infarction [ 37 ]. However, the odds of cardiovascular events in patients with early coronary heart disease manifestations were the highest in patients with an elevated LMR [ 38 ]. Lombardi et al also found that a higher LMR is directly associated with any type of clinical diagnosis of dementia [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis is based on a simple marker, easily obtained from whole blood count analysis, which serves as a predictive marker for perioperative significant AB block (2nd or 3rd degree requiring pacing). The relation between preoperative simple inflammatory markers and cardiovascular diseases progression has already been postulated [ 33 , 34 , 35 , 36 ]. We focused on preoperative inflammatory indices in children, as previous reports in adults linked postoperative complications to perioperative neutrophil activation [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%